0225 Do Associations Between Daily Stress and Sleep Vary by Work Shift? A Within-Person Analysis in Nurses. (27th May 2020) - Dietch, J R; Slavish, D C; Messman, B; Wardle-Pinkston, S; Kelly, K; Ruggero, C J; Taylor, D J
Abstract: Introduction: Longitudinal studies have shown daily stress and sleep are bidirectionally associated. Nurses are particularly likely to experience sleep disturbances and high stress due to demanding work environments. Night shift work may be a unique stressor for nurses that exacerbates associations between stress and sleep. Using a within-person design, we examined the daily bidirectional associations between stress and sleep and moderation by nightly work shift (day/off shift vs. night shift) in a large sample of nurses. Methods: Participants were 393 nurses (91% female; 77% white, mean age = 38.4 years) recruited from two hospitals. Participants completed 14 days of sleep diaries and actigraphy to assess total sleep time (TST) and sleep efficiency (SE). They simultaneously completed assessments of stress on the previous day (0 = "not at all" to 4 = "extremely") and daily work schedule (day/off shift vs. night shift [work between 9pm-6am]). Results: Results indicated greater daily stress was associated with shorter diary TST (b = -9.49, p<.0001) and actigraphy TST (b = -4.48, p<.01), as well as lower diary SE (b = -0.56, p<.001). When examining reverse pathways of sleep predicting next day stress, both diary TST (b = -0.0004, p<.0001) and actigraphy TST (b = -0.0002, p = .03) predicted higher next-day stress. Lower diary SE predicted higher next-day stress (b = -0.005, p<.001). Only the association between daily stress and nightly diary SE was moderated by daily work shift: only when nurses worked a day or off shift did they have a negative association between daily stress and diary SE (b = -0.68, p<.0001). Conclusion: Daily stress and sleep disturbances occurred in a bidirectional fashion for night- and day-shift working nurses. Most associations were similar regardless of daily type of work shift. Objective and subjective short TST and low subjective SE may contribute to a cycle of increased stress and are prime targets for a tailored sleep intervention in nurses. More research is needed to develop interventions to address the unique sleep health challenges faced by nurses. Support: NIAID R01AI128359-01